A regioselectively 1, 1′, 3, 3′-tetrazincated ferrocene complex displaying core and peripheral reactivity. Issue 25 (1st April 2020) - Honeyman, Gordon W.; Armstrong, David R.; Clegg, William; Hevia, Eva; Kennedy, Alan R.; McLellan, Ross; Orr, Samantha A.; Parkinson, John A.; Ramsay, Donna L.; Robertson, Stuart D.; Towie, Stephen; Mulvey, Robert E.
Abstract : A tetrazincated ferrocene complex displays divergent basicity towards aromatic substrates through either its core or peripheral ligands. Abstract : Regioselective 1, 1′, 3, 3′-tetrazincation [C–H to C–Zn( t Bu)] of ferrocene has been achieved by reaction of a fourfold excess of di- t -butylzinc ( t Bu2 Zn) with sodium 2, 2, 6, 6-tetramethylpiperidide (NaTMP) in hexane solution manifested in the trimetallic iron–sodium–zinc complex [Na4 (TMP)4 Zn4 ( t Bu)4 (C5 H3 )2 Fe], 1 . X-ray crystallographic studies supported by DFT modelling reveal the structure to be an open inverse crown in which two [Na(TMP)Zn( t Bu)Na(TMP)Zn( t Bu)] 2+ cationic units surround a (C5 H3 )2 Fe 4− tetraanion. Detailed C6 D6 NMR studies have assigned the plethora of 1 H and 13 C chemical shifts of this complex. It exists in a major form in which capping and bridging TMP groups interchange, as well as a minor form that appears to be an intermediate in this complicated exchange phenomenon. Investigation of 1 has uncovered two distinct reactivities. Two of its peripheral t -butyl carbanions formally deprotonate toluene at the lateral methyl group to generate benzyl ligands that replace these carbanions in [Na4 (TMP)4 Zn4 ( t Bu)2 (CH2 Ph)2 (C5 H3 )2 Fe], 2, which retains its tetrazincated ferrocenyl core. Benzyl-Na π-arene interactions are a notable feature of 2 . In contrast, reaction with pyridine affords the crystalline product [Na·4py][Zn(py*)2 ( t Bu)·py]∞, 3, where py is neutral pyridine (C5 H5 N) and py* is the anion (4-C5 H4 N), a rare example of pyridine deprotonated/metallated at the 4-position. This ferrocene-free complex appears to be a product of core reactivity in that the core-positioned ferrocenyl anions of 1, in company with TMP anions, have formally deprotonated the heterocycle.